2020
DOI: 10.1177/2048872620903453
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation as temporary bridge to definitive treatment of ventricular arrhythmia storm

Abstract: Background: Electrical storm and incessant ventricular tachycardia (VT) are characterized by the clustering of episodes of VT or ventricular fibrillation (VF) and are associated with a poor prognosis. Autonomic nervous system activity influences VT threshold, and deep sedation may be useful for the treatment of VT emergencies. Methods: We reviewed data from conscious patients admitted to our intensive care unit (ICU) due to monomorphic VT, polymorphic VT or VF at our tertiary center between 2010 and 2018. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The recommendations in the guidelines are unreferenced. A small study by Bundgarrd et al suggested that deep sedation and intubation reduced or terminated VT in patients with refractory to guideline-recommended usual clinical care in the acute setting [ 9 ]. It can be used as a bridge to definitive treatment in patients with different underlying cardiac disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations in the guidelines are unreferenced. A small study by Bundgarrd et al suggested that deep sedation and intubation reduced or terminated VT in patients with refractory to guideline-recommended usual clinical care in the acute setting [ 9 ]. It can be used as a bridge to definitive treatment in patients with different underlying cardiac disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Its side effects include bradycardia, hypotension, respiratory depression, hypertriglyceridemia, and propofol infusion syndrome. Still, no RCTs have been found [ 2 , 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep sedation and mechanical ventilation have successfully controlled drug-refractory ES. 140 , 141 An acute response, defined as the termination of ES within 15 min without recurrent episodes over the following 24 h, occurred in 47% of a mixed cohort of 116 ES patients who were refractory to AADs. Response to deep sedation was an independent predictor of in-hospital survival.…”
Section: Acute Managementmentioning
confidence: 99%
“…catheter ablation, coronary revascularization, therapeutic optimization) or resolution of possible reversible causes. 11 …”
Section: Sedationmentioning
confidence: 99%